An Asessment of the Effectiveness of Internal Control System at the Local Government Level in Nigeria: A Case Study of Kaduna South-Local Government - Maryam, Abdullahi Habib (2011)
The focus of this research work in general is to assess the effectiveness or otherwise of internal control system at local government level, problems and prospects with specific reference to Kaduna south Local Government, Kaduna State. This study work was started by introducing the general background of the subject matter in chapter one. These include statement of the problem, the objective of the study, the research hypotheses, the significance of the study, the scope of the study, limitation of the study, and operational definition. Chapter two is the literature review, which contained the views of some scholars and intellectuals as regard to the topic under study. It covered the concepts of internal control and the internal control system, features of internal control, effective internal control system, link between internal audit and internal control and internal control system at the local government level. Chapter three covers the research methodology, research framework, the chapter comprises of population of the study, sample size, sampling techniques, methods of data collection and data analysis. Chapter four which is the main concern of the study covers the presentation of data, analysis, test of hypotheses of the study and the summary of findings. Finally, Chapter five covers the summary of the research, conclusions and recommendations based on the findings of the study.